Introduction of a quality management system compliant with DIN EN ISO 9001:2000 into a university department of nuclear medicine - Jansen-Schmidt, V.; Paschen, U.; Kröger, S.; Bohuslavizki, K. H.; Clausen, M. (Nuklearmedizin - NuclearMedicine, 2001)
In 1995, the management of the University Clinic Hamburg-Eppendorf proposed to establish a total quality assurance (QA) system. A revised QA-system has been introduced stepwise in the department of nuclear medicine since 1997, and certification was achieved in accordance with DIN EN ISO 9001:2000 on February 14,2001.The QA-handbook is devided into two parts. The first part contains operational (diagnostic and therapeutic) procedures in so-called standard operating procedures (SOP). They describe the indication of procedures as well as the competences and time necessary in a standardized manner. Up to now, more than 70 SOPs have been written as a collaborative approach between technicians and physicians during daily clinical routine after analysing and discussing the procedures. Thus, the results were more clearly defined processes and more satisfied employees.The second part consists of general rules and directions concerning the security of work and equipment as well as radialion protection tasks, hygiene etc. as it is required by the law. This part was written predominantly by the management of the department of nuclear-medicine and the QA-coordinator. Detailed information for the patients, documentation of the work-flows as well as the medical report was adapted to the QM-system. Although in the introduction phase of a QA-system a vast amount of time is necessary, some months later a surplus for the clinical workday will become available. The well defined relations of competences and procedures will result in a gain of time, a reduction of costs and a help to ensure the legal demands. Last but not least, the QA-system simply helps to build up confidence and acceptance both by the patients and the referring physicians.
Keywords: Quality assurance system; ISO 9001:2000; university department; nuclear medicine